2020
DOI: 10.1002/admt.201900991
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Highly Dense Silk Fibroin Biomemristor Array and Its Resistive Switching Characteristics

Abstract: Development of polymeric memristors is of great interest for wearable and implantable applications because of its flexibility and transparency. One of distinguished polymeric memristor materials is silk fibroin, which is a biodegradable protein extracted from Bombyx mori cocoons. However, fibroin memristors demonstrated earlier show low memory cell density (<100 cells mm−2). In this paper, silk fibroin memristors with cell density 25 times higher than that of the previously reported silk fibroin memristors by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…[116] Among the several types of memory devices, protein-based memristors exhibit typical resistive switching memory properties with other beneficial features such as biocompatibility, flexibility, and bio-resorbability, and have thus been applied in implantable electronic devices. [97,[118][119][120] Owing to the natural abundance and low cost, protein materials have emerged as excellent candidates for the development of bio-integrated electronic devices. [118] Recently, protein materials such as SF, egg albumen, keratin, ferritin, collagen, S-layer protein, and sericin have been developed for the construction of biodegradable and biocompatible memristors.…”
Section: Memristorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[116] Among the several types of memory devices, protein-based memristors exhibit typical resistive switching memory properties with other beneficial features such as biocompatibility, flexibility, and bio-resorbability, and have thus been applied in implantable electronic devices. [97,[118][119][120] Owing to the natural abundance and low cost, protein materials have emerged as excellent candidates for the development of bio-integrated electronic devices. [118] Recently, protein materials such as SF, egg albumen, keratin, ferritin, collagen, S-layer protein, and sericin have been developed for the construction of biodegradable and biocompatible memristors.…”
Section: Memristorsmentioning
confidence: 99%
“…[133] After extensive research in recent years, SF has been proved to successfully achieve the typical resistive switching performance and can be fabricated as a memristor array, as well as, emulate both the synaptic structures and function, exhibiting significant potential in the nonvolatile random access memory applications. [97,120] However, most studies have utilized the inherent characteristics of SF materials such as solution processability, excellent biocompatibility, low weight, and controllable biodegradation, but development in terms of the mesoscopic structural modification has been lacking. Conventional protein-based memristors are restricted by the inherent disadvantages of protein materials under external electrical field, that is, random ion deposition and unstable structure, leading to low switching speed, high operating voltage, and inferior endurance property.…”
Section: Memristorsmentioning
confidence: 99%
“…Organic materials often show better flexibility than inorganic materials, which are potential candidates for fabricating flexible memristive devices and arrays. Common organic materials, such as albumin (Chen et al, 2015), collagen (Zeng et al, 2019), silk fibroin (Kook et al, 2020;Wang et al, 2016a), polyethyleneimine (PEI) (Yang et al, 2020) and poly(1,3,5-trivinyl-1,3,5trimethylcyclotrisiloxane) (pV 3 D 3 ) (Jang et al, 2019;Jang J. et al, 2018a), have demonstrated their promising application in flexible memristive devices and arrays. By employing waferscale ultraviolet photolithography technology, a silk fibroin-based memristive array was successfully fabricated on a parylene-C film with robust flexibility (Kook et al, 2020).…”
Section: Flexible Organic Memristive Arraysmentioning
confidence: 99%
“…Common organic materials, such as albumin (Chen et al, 2015), collagen (Zeng et al, 2019), silk fibroin (Kook et al, 2020;Wang et al, 2016a), polyethyleneimine (PEI) (Yang et al, 2020) and poly(1,3,5-trivinyl-1,3,5trimethylcyclotrisiloxane) (pV 3 D 3 ) (Jang et al, 2019;Jang J. et al, 2018a), have demonstrated their promising application in flexible memristive devices and arrays. By employing waferscale ultraviolet photolithography technology, a silk fibroin-based memristive array was successfully fabricated on a parylene-C film with robust flexibility (Kook et al, 2020). The fabricated memristive crossbar array shows robust flexibility (bendable to a radius of 1.3 mm) and reliable electrical performance (Figure 2D).…”
Section: Flexible Organic Memristive Arraysmentioning
confidence: 99%
“…[54,55] The broadband monotonic absorption ranging from the ultraviolet (UV) to the near-infrared (NIR) region [56] and the movement of charge carriers through the -system in PDA would lead to strong photothermal conversion and photonto-current conversion ability by irradiating the materials with protons above the relevant optical gaps. [57][58][59][60][61] It is thus highly attractive to serve as endogenous photoacoustic contrast agent, photothermal conversion agent and photoelectric material. [62][63][64][65] Moreover, the -electron-rich interfaces in PDA make them pow-erful to bind with various electron-rich molecules viastacking and -cation interactions.…”
Section: Surface Modificationmentioning
confidence: 99%